Association of maxillofacial injuries with traumatic brain injuries in paediatric patients: a case-control study - Suprabha, Baranya Shrikrishna; Wilson, Michael Lowery; Baptist, Joanna; Subramanian, Sadhvi Shankar; Shenoy, Ramya; Jahanjoo, Fatemeh; Radhakrishnan, Jeedhu; Kamath, V. Mayur; Anagha, N. P.; Chaurasia, Diksha (BMC, 2025)
Background Traumatic brain injuries (TBIs) are among the most challenging conditions to accurately diagnose in children, and many TBIs are underdiagnosed. Patients with maxillofacial injury may be at risk for TBI. The objective of this study was to analyse the association between maxillofacial injuries and TBI among paediatric patients. Analysis of the factors associated with the occurrence of TBI among paediatric patients with maxillofacial injuries was the secondary objective.
Method This case-control study included 192 cases defined as paediatric patients with maxillofacial injuries and 192 controls defined as all paediatric patients with traumatic injuries to other body locations and with no maxillofacial injuries. The medical records of patients aged 0-18 years, who underwent treatment at a tertiary care hospital were screened. Patient demographic data, causes of trauma, and the presence, type, and severity of TBI were recorded. For the cases, the presence of facial fracture, type and severity of the maxillofacial injuries were recorded. The odds ratio was obtained to determine the association between maxillofacial injuries and TBI. Multiple logistic regression analysis was performed to study the associations of all the recorded study variables with the occurrence of TBI in patients with maxillofacial injuries.
Results A statistically significant difference was seen between the cases and controls for TBI occurrence, with 53% of cases recording TBI, compared to 32% among controls, with an odds ratio of 2.5. Multiple logistic regression analysis with the presence/absence of TBI among the cases as the dependent variable revealed a significant association of road traffic accidents (RTA), longer duration of hospital stays, and dentoalveolar fracture with TBI.
Conclusion Paediatric patients with maxillofacial injuries need to be screened for TBI, as the risk of occurrence of TBI is 2.5 times greater in these patients than in those with injuries involving other parts of the body. RTA and prolonged hospitalization are factors associated with TBI among paediatric patients with maxillofacial injuries. The presence of only dentoalveolar injuries decreases the likelihood of a TBI.